Impact of self-heating effect on the performance of hybrid FinFET. (June 2018) - Nelapati, Rajeev Pankaj; K, Sivasankaran
Abstract: In this paper, we presented the impact of self-heating effect (SHE) in hybrid FinFET, which is a promising device for high-performance applications. The impact of variation of channel length (Lg ), fin width (Wfin ), buried oxide thickness (tbox ), the pitch of the device (Lpitch ) and a number of fins (N) on the increase in lattice temperature for hybrid FinFET is observed. The linear dependence of thermal resistance (Rth ) on Lg, Wfin, and tbox ; and nonlinear dependence on Lpitch and N is studied. It is seen that unlike trigate FinFET, hybrid FinFET have the advantage of increased drain current from 50 μA to 103 μA with an increase in Lpitch from 50 nm to 250 nm, also reduces lattice temperature from 726.5 K to 495.6 K.